ANALYSIS OF CENTRAL WESTERN EUROPE DEFORMATION USING GPS AND SEISMIC DATA - Tesauro M.; Hollenstein C.; Egli R.; Geiger A.; Kahle H.-G. (My University, 2006)
The kinematic field of central western Europe is characterized by relatively small movements (around 1-2 mm/year) and diffuse seismicity with earthquakes occurring mostly in the shallow crust (within 15 km), prevalently concentrated along the Alps and the European Cenozoic Rift System (ECRIS). In order to study and constrain the current crustal kinematic field we reconstructed the velocity and the strain field using permanent GPS stations, belonging to different networks (AGNES, EUREF, REGAL, RGP). The 2D strain rate tensor has been calculated using the method of least-squares collocation. Our results show that the area of maximum compression is located along the Alpine chain, where maximum values of 7 ± 2 nstrain/year are found, while maximum extension is measured between the Armorican Massif and the Massif Central, where values of 4 ± 2 nstrain/year are reached. The earthquakes with M > 3.0, have been used to estimate the seismic strain rates, while the style of the seismic deformation was reconstructed from the fault plane solutions (FPS) available from the literature. Relatively high values of seismic strain rates (around 10 nstrain/year) are measured along the Alpine Chain and the ECRIS. Results obtained by geodetic and seismic data are quite in agreement and reflect the different tectonic evolution of the geological features characterizing the area of study. The orientation of the compressional geodetic and seismic strain axes are NW-SE in most of the area of study, on account of the action of plate boundary forces. A rotation of the same axes to N-S direction along the eastern Alps, possibly related to the Adria convergence, is found. © 2006 Elsevier Ltd. All rights reserved.
Keywords: GEOPHYSICS; GPS; SEISMIC; STRAIN FIELD; TECTONICS